Principles and Practice of Geriatric Surgery - Rosenthal, Ronnie Ann.; Zenilman, Michael E.; Katlic, Mark R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
"In the preface to this impressive and well-produced book, the editors state that their aim is not to describe a new surgical specialty, since most surgeons will soon need to be "geriatric surgeons," but to assemble a comprehensive account that will allow "all providers of healthcare to the elderly to understand the issues involved in choosing surgery as a treatment option for their patients." This is a useful book that deserves to do well. I hope that the editors and their publisher will have the stamina to make this the first of several editions, as it is clear that updated information about surgery in the elderly will be required to keep pace with this important field." NEJM Book Review
PART I- GENERAL PRINCIPLES -- Section 1- Physiology of Aging -- Invited Commentary -- Cellular and Molecular Aging -- Cancer, Carcinogenesis and Aging -- Effects of Aging on Immune Function -- Hematological Changes, Anemia and Bleeding -- Invited Commentary -- Nutrition and Metabolism -- Wound Healing and Aging -- Frailty and Surgery in the Elderly -- Section 2 - Social/Societal Issues -- Invited Commentary -- Demography of Aging and Disability -- Economics of Providing Surgical Care to an Aging Population: Implications for the Surgical Workforce -- Defining Quality of Care in Geriatric Surgery -- Ethics in Clinical Practice -- Teaching Geriatrics to Surgeons -- Palliative Care and Decision Making at the End of Life -- Surgery in Centenarians -- The Effects of Advanced Age on Physician Performance -- Section 3- Perioperative Issues -- Invited Commentary -- Principles of Geriatric Surgery -- Geriatric Models of Care -- Preoperative Evaluation of the Older Surgical Patient -- Invited Commentary -- Physiologic Response to Anesthesia in the Elderly -- Choosing the Best Anesthetic Regimen -- Acute Perioperative Pain Management in Elderly Patients -- Drug Usage in Surgical Patients: Preventing Medication-Related Problems -- Invited Commentary -- Common Perioperative Complications in Older Patients -- Management and Outcomes of Intensive Care in the Geriatric Surgical Patient -- Care of the Injured Elderly -- Maximizing Postoperative Functional Recovery -- PART II SPECIFIC ISSUES -- Section 1- Endocrine System/Breast -- Invited Commentary -- Surgcial Disorders of the Thyroid in the Elderly -- Parathyroid Disorders in the Elderly -- Adrenal Tumors in Older Persons -- Benign Breast Disease in Elderly Women and Men -- Breast Cancer in Elderly Women -- Diabetes in the Elderly -- Section 2- Oral Cavity, Eyes, Ears, Nose and Throat -- Invited Commentary -- Changes in the Oral Cavity with Age -- Geriatric Ophthalmology -- Anatomic and Physiologic Changes of the Ears, Nose, and Throat -- Geriatric Dysphagia -- Head and Neck Cancer in the Elderly -- Section 3 - Respiratory System -- Invited Commentary -- Physiologic Changes in Respiratory Function -- Pulmonary Surgery for Malignant Disease in the Elderly -- Section 4 - Cardiovascular System -- Invited Commentaries -- Physiologic Changes in Cardiac Function with Age -- Risk Factor for Atherosclerotic Disease in the Elderly -- Cardiac Surgery -- Surgical Treatment of Vascular Occlusive Disease -- Natural History and Treatment of Extracranial Cerebrovascular Disease -- Natural History and Treatment of Aneurysms -- Section 5 - Gastrointestinal System -- Invited Commentary -- Physiologic Changes of the Gastrointestinal Track -- Benign Esophageal Disease -- Esophageal Cancer in the Elderly -- Benign Diseases of the Stomach and Duodenum -- Gastric Cancer in the Elderly -- Small Bowel Obstruction in Geriatric Patients -- Lower Gastrointestinal Bleeding in the Elderly -- Ishcemic Disorders of the Large and Small Bowel -- Inflammatory Bowel Disease -- Diverticulitis and Appendicitis in the Elderly -- Benign Colorectal Disease -- Neoplastic Diseases of the Colon and Rectum -- Abdominal Wall Hernia in the Elderly -- Section 6 - Hepatobiliary System -- Invited Commentary -- Hepatobiliary and Pancreatic Function: Physiologic Changes -- Benign Disease of the Gallbladder and Pancreas -- Malignant Diseases of the Gallbladder and Bile Ducts -- Benign and Malignant Neoplasms of the Exocrine Pancreas -- Benign and Malignant Tumors of the Liver -- Section 7- Urogenital System -- Invited Commentaries -- Change in Renal Function, Fluids and Electrolytes -- Urinary Incontinence -- Neoplasms of the Kidney, Ureters and Bladder -- Benign and Malignant Diseases of the Prostate -- Benign Gynecological Disorders in Older Women -- Gynecological Malignancies in the Elderly -- Section 8 - Nervous System -- Invited Commentary -- Effects of Aging on the Nervous System -- Geriatric Neurosurgical Emergencies -- Benign and Malignant Tumors of the Brain -- Spinal Disorders and Nerve Compression Syndromes -- Section 9- Musculoskeletal System and Soft Tissue -- Invited Commentary -- Physiologic Changes of the Bones and Soft Tissue with Age -- Benign and Malignant Lesions of the Skin in Old Age -- Surgical Management of Soft Tissue Sarcoma in the Geriatric Population -- Pressure Sores in the Elderly -- Orthopedic Trauma in the Elderly -- Treatment of Degenerative Joint Diseases -- Section 10- Transplantation -- Invited Commentary -- Elderly Donors in Transplantation -- Elderly Transplant Recipients.
Keywords: Medicine; Geriatrics; Surgery; Abdomen -- Surgery; Colon (Anatomy) -- Surgery; Endoscopic surgery; Medicine & Public Health; Surgery; Geriatrics/Gerontology.; General Surgery; Minimally Invasive Surgery; Colorectal Surgery; Abdominal Surgery